Quantifying fission yields at the National Ignition Facility using depleted uranium foil experiments - A. C. Hayes; Gerard Jungman; J. D. Martin; G. Rusev; E. N. Loomis; L. Kot; H. Geppert-Kleinrath; Justin Jeet; C. A. Velsko (AIP Advances)
There are programs for high-Z shell experiments at the National Ignition Facility (NIF). For shells made of actinide material, a quantitative fission diagnostic is needed in order to determine how much fission took place and whether the fission was sufficient to produce a non-negligible heat source in the burning capsule. Here, we present a viable coupled experimental and theoretical technique for making quantitative fission measurements possible. The proposed scheme involves using a well-characterized set of depleted uranium foils outside an NIF capsule to verify the conversion of xenon and krypton fission fragments collected at the Radiochemical Analysis of Gaseous Samples (RAGS) facility into total fission yield. We present the calculations needed for this conversion, including the decays in and out of fission fragment chains during the RAGS pump-down of the NIF chamber.